Bureaucratic Barriers and Freedom of Enterprise: Analysis of the Administrative Implications of Labor Regulation (Euro-Latin American Journal of Administrative Law, 2024)
The authors analyze the effects of the recent modifications to the elimination and prevention of bureaucratic barriers procedure on the regulation of labor outsourcing and collective relations, in which it has been incorporated. In this context, it is evaluated whether it is possible to denounce the indirect effects produced by labor regulation on business activity. Finally, some aspects and factors to be considered for this purpose are presented.